2019
DOI: 10.1109/jproc.2019.2901215
|View full text |Cite
|
Sign up to set email alerts
|

The Service Value Method for Design of Energy Access Systems in the Global South

Abstract: This paper presents the Service Value Method as a novel means to gather and interpret end-user needs, aspirations, and contextual factors to improve engineering design practice of energy access systems for the Global South. The method adopts a service-oriented approach and consists of a rapid and effective field exercise to gather qualitative and quantitative data from end-users in focus groups. This exercise is suitable for enabling end-user participation in Global South contexts. The data is interpreted as S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The study results have shown that potential conflicts from proposed renewable energy projects are more likely to be identified at ESIA stage when stakeholder participation is in workshops as opposed to public meetings (baraza) and public hearings. The ultimate aim is to contribute to the facilitation of access to clean, reliable and affordable energy at the lowest level of the pyramid to generate income and improve quality of life [59]. Public participation, a constitutional and legislative requirement during ESIA process in Kenya [33], is an innovative way of bringing on board all those likely to be affected by an energy project decision to have an input into that decision using appropriate procedures [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results have shown that potential conflicts from proposed renewable energy projects are more likely to be identified at ESIA stage when stakeholder participation is in workshops as opposed to public meetings (baraza) and public hearings. The ultimate aim is to contribute to the facilitation of access to clean, reliable and affordable energy at the lowest level of the pyramid to generate income and improve quality of life [59]. Public participation, a constitutional and legislative requirement during ESIA process in Kenya [33], is an innovative way of bringing on board all those likely to be affected by an energy project decision to have an input into that decision using appropriate procedures [60].…”
Section: Discussionmentioning
confidence: 99%
“…Public participation, a constitutional and legislative requirement during ESIA process in Kenya [33], is an innovative way of bringing on board all those likely to be affected by an energy project decision to have an input into that decision using appropriate procedures [60]. Studies have shown that integration of energy end-user needs, sociocultural factors and local context in the overall energy project design avoid failed or ineffective energy project [59]. In this way local knowledge is exhaustively harnessed and incorporated in environmental decision making [33].…”
Section: Discussionmentioning
confidence: 99%
“…The SoNG methodology differs from other electricity providers as it starts with development as the aim and electricity as the means, whereas traditional utility models begin with electricity provision assuming development will follow. The process begun with an in depth community consultation identifying the key priorities and conducting service value tests [63] to quantify the specific desired services and productive uses in the community. This was followed by a system design and costing exercise, testing the community willingness to pay and checking for any technical constraints.…”
Section: Solar Nanogrid (Song) Projectmentioning
confidence: 99%
“…They are easy to deploy either in a standalone mode or as part of another power grid. Widespread implementation of microgrids incorporating nanogrids could rapidly increase the social impact of electricity, reaching up to 900 million people [2], with two thirds of them in sub-Saharan Africa [3]. Designing economic systems and embedding smart solutions is the best combination for an extra robust low-cost energy distribution grid.…”
Section: Introductionmentioning
confidence: 99%